2020
DOI: 10.1177/1475921720972926
|View full text |Cite
|
Sign up to set email alerts
|

A review on diagnostic and prognostic approaches for gears

Abstract: Prognostics and health management has become a significant part of component life-cycle in modern industries. The prognostics and health management framework is implemented in the industries to identify the fault type, assess fault severity, and predict the future state or remaining useful life to optimize the maintenance activities. Three significant aspects of a prognostics and health management framework are diagnostics, prognostics, and decision making. This article presents a review of different types of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 278 publications
0
23
0
Order By: Relevance
“…The American Gear Manufacturing Association (AGMA) classified 36 failure mechanisms of gears into seven categories: wear, scuffing, surface fatigue, plastic flow, cracking, bending fatigue, and breakage. The gear failure is classified into two categories: lubricated and non-lubricated [2,[67][68][69][70]. Sliding wear, scoring, plastic flow, surface fatigue, cracking, fracture, and bending fatigue are the most common causes of gear failure.…”
Section: List the Possible Failure Modesmentioning
confidence: 99%
See 2 more Smart Citations
“…The American Gear Manufacturing Association (AGMA) classified 36 failure mechanisms of gears into seven categories: wear, scuffing, surface fatigue, plastic flow, cracking, bending fatigue, and breakage. The gear failure is classified into two categories: lubricated and non-lubricated [2,[67][68][69][70]. Sliding wear, scoring, plastic flow, surface fatigue, cracking, fracture, and bending fatigue are the most common causes of gear failure.…”
Section: List the Possible Failure Modesmentioning
confidence: 99%
“…The gears are the most efficient way to transmit the power [1]. It is found that most gears are failed 74% of time due to the service-related causes and 23% due to design and manufacturing errors [2]. The servicesrelated failures are due to consistent overloading, torque fluctuations, improper installation, improper lubrication, contamination of foreign particles, operational errors and so on.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These indicators signalise potential machinery faults and are subjected to classification processes (e.g., k nearest neighbours or principal component analysis) [26,30]. References [31,32] propose correlation-based degradation parameters extracted from gearbox residual vibration signals. This approach allows the identification of multiple stages of natural pitting progression.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, the prognostic approaches in a PHM framework can be implemented in three different ways: physics-based approaches, data-driven approaches, and hybrid approaches (a combination of data-driven and physics-based approaches) [ 1 ]. By solving a set of equations based on the physical laws and the knowledge of engineering and science, the physics-based prognostic approaches assess the component health and predict when the damage crosses a predefined failure threshold based on the mathematical modeling of the degradation process for a particular failure mode [ 2 ]. However, with high accuracy and efficiency requirements in component RUL prediction, physical model-based life prediction methods are difficult to meet modern needs due to their complexity, time-consuming, and nonuniversality.…”
Section: Introductionmentioning
confidence: 99%